(3CLhHI eSGFd OYhI GdCWHGA dGHf HWdGfs - (3Ydj Hf gHI Gddg Hf Ydj Hf GdMSjf, CHh GdMSf GHf CKQOj , J HYO (B507 (3g`s; (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s ((3YHO GdbGOQ Hf NjQ GdOjf Hf HGjRjO GdLfOQi s)
(3ChdgG (B:s
(3SCdJi CjOc Gddg EjVGM GdeSGFd GdJi ChOYgG GdTjN CHh GdMSf Hf HWdGf QMeg Gddg ai ebGdJg GdehSheI HOYhI GdCWHGA s
(3BNQgG (B:s
(3hfMf fTGgO GdehdOjf SGYI hdGOJge bHd Cf jZJPhG HGddHf Ch HZjQg jJHQRhf TjFkG jejd Edi GdShGO ebOGQg jSjQ hGdYQH JSejg GdYbi agPG aVdI Ci TF gh ? JeJ s
(3Vef eLehY s
(3GdeDda cGf MjkG SfI (B507(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs